Phthalates Implications in the Cardiovascular System - Mariana, Melissa; Cairrao, Elisa (Journal of cardiovascular development and disease, 2020)
Today’s sedentary lifestyle and eating habits have been implicated as some of the causes of the increased incidence of several diseases, including cancer and cardiovascular diseases. However, environmental pollutants have also been identified as another possible cause for this increase in recent decades. The constant human exposure to plastics has been raising attention regarding human health, particularly when it comes to phthalates. These are plasticizers used in the manufacture of industrial and consumer products, such as PVC (Polyvinyl Chloride) plastics and personal care products, with endocrine-disrupting properties, as they can bind molecular targets in the body and interfere with hormonal function. Since these compounds are not covalently bound to the plastic, they are easily released into the environment during their manufacture, use, or disposal, leading to increased human exposure and enhancing health risks. In fact, some studies have related phthalate exposure with cardiovascular health, having already shown a positive association with the development of hypertension and atherosclerosis in adults and some cardiometabolic risk factors in children and adolescents. Therefore, the main purpose of this review is to present and relate the most recent studies concerning the implications of phthalates effects on the cardiovascular system.